FIGHT AGAINST DESTRUCTIVE IDEAS - A TOOL TO PRESERVE THE SPIRITUAL SPACE (TAMADDUN NURI JURNALI, 2024)
This article examines the importance of constructive ideas in creating a new spiritual space and the role of combating destructive ideas. Suggestions and recommendations were also made regarding methods and means of developing ideological immunity against destructive ideas such as extremism, terrorism, radicalism, xenophobia, and mass culture.